Group Dynamic Courseware (GDC): Innovative Strategic Intervention in Enhancing Basic Mathematical Skills - Rabor, Joyce Neniel; Sumilang, Maria Sheila Hermano; Opinio, Kathreen Merwin Neniel (JPAIR Multidisciplinary Research, 2020)
Grade 4 pupils got a low MPS score of 11.11 % in the Mathematics pre-test conducted at Banlic Elementary School Division of Calamba, Laguna. As an intervention, the researchers developed Group Dynamics Courseware (GDC) that aimed at enhancing the basic Mathematical skills of the pupil-respondents. The effectiveness of the Group Dynamic Courseware (GDC) was checked through a pre-test and post-test written assessment. The result revealed a mean difference between the pre-test and post-test results of -10.87, which means a significant increase in the academic performance of the pupils after the integration of the courseware. Furthermore, t Stat of the pre and post-test was -14.022 > 2.015 critical value with forty-four (44) degrees of freedom and a .000 level of significance. Thus, this directly implies that the Null hypothesis is rejected; therefore, there is a significant difference in the academic performance of the pupil respondents after the integration of Group Dynamic Courseware. As supported by the pupils’ reflection, data revealed that the Group Dynamic Courseware is Highly Effective regarding instruction and pupils' activities. The researchers concluded that GDC in Mathematics had a significant impact on the pupils’ academic performance. Pupils were motivated and engaged in hands-on activities, collaborate with the groups to accomplish an essential task within the prescribed time.
Keywords: courseware; mixed-method; innovative; Banlic Elementary School; Calamba City; Philippines